MODERN MODELS OF PEDAGOGICAL EDUCATION AND PROFESSIONAL TRAINING (Web of Teachers: Inderscience Research, 2024)
The article analyzes current trends in the training of pedagogical specialists. Innovative technologies used in teacher education and the importance of their use are also explored.